Integrated Use of Herbicide and Weed Mulch with Closer Spacing for Weed Management in Dry Direct Seeded Rice - Malik, Sagarika; Duary, B.; Jaiswal, D. K. (International Journal of Bio-resource and Stress Management, 2021)
The field experiments were conducted during the wet season of 2015 and 2016 (June to October) at Agricultural Farm, Institute of Agriculture, Visva-Bharati, Sriniketan, India to study the impact of integrated use of weed mulch and herbicide with closer spacing on weed growth and yield of direct seeded dry sown rice (Oryza sativa L.) cultivar MTU 1010. The experiment consisted of twelve treatments involving sole or integrated application of pre-emergence herbicide pendimethalin, mulching with water hyacinth and Indigofera weed and closer row spacing of 20 cm. The experiment was laid out in randomized block design with three replications. The experimental field was infested with 14 weeds out of which the predominant species were Cynodon dactylon, Echinochloa colona, Cyperus iria, Ludwigia parviflora, Hydrolea zeylanica, Spilanthes acmella, Alternanthera sessilis, Commelina benghalensis and Cyanotis axillaris. Integration of pendimethalin at 0.75 kg ha-1 and mulching with water hyacinth and closer spacing reduced weed dry weight by 75.92% over the weedy check. Integration of mulching with water hyacinth and closer spacing increased grain yield by 37.27 and 41.12% over sole application of pendimethalin and water hyacinth mulch, respectively. Weed competition resulted in 57% reduction in grain yield of rice. Hand weeding twice (25 and 45 DAS) had a significant effect on the reduction of weed density and dry weight and increasing grain yield of rice which was followed by application of pendimethalin 0.75 kg ha-1 along with mulching with water hyacinth at a closer row spacing of 20 cm.